Experimental Oral Herpes Simplex Virus-1 (HSV-1) Co-infection in Simian Immunodeficiency Virus (SIV)-Infected Rhesus Macaques - Aravantinou, Meropi; Mizenina, Olga; Calenda, Giulia; Kenney, Jessica; Frank, Ines; Lifson, Jeffrey D.; Szpara, Moriah; Jing, Lichen; Koelle, David M.; Teleshova, Natalia; Grasperge, Brooke; Blanchard, James; et al. (Frontiers in Microbiology, 2017)
Herpes simplex virus 1 and 2 (HSV-1/2) similarly initiate infection in mucosal epithelia and establish lifelong neuronal latency. Anogenital HSV-2 infection augments the risk for sexual human immunodeficiency virus (HIV) transmission and is associated with higher HIV viral loads. However, whether oral HSV-1 infection contributes to oral HIV susceptibility, viremia, or oral complications of HIV infection is unknown. Appropriate non-human primate (NHP) models would facilitate this investigation, yet there are no published studies of HSV-1/SIV co-infection in NHPs. Thus, we performed a pilot study for an oral HSV-1 infection model in SIV-infected rhesus macaques to describe the feasibility of the modeling and resultant immunological changes. Three SIV-infected, clinically healthy macaques became HSV-1-infected by inoculation with 4 × 108 pfu HSV-1 McKrae on buccal, tongue, gingiva, and tonsils after gentle abrasion. HSV-1 DNA was shed in oral swabs for up to 21 days, and shedding recurred in association with intra-oral lesions after periods of no shedding during 56 days of follow up. HSV-1 DNA was detected in explant cultures of trigeminal ganglia collected at euthanasia on day 56. In the macaque with lowest baseline SIV viremia, SIV plasma RNA increased following HSV-1 infection. One macaque exhibited an acute pro-inflammatory response, and all three animals experienced T cell activation and mobilization in blood. However, T cell and antibody responses to HSV-1 were low and atypical. Through rigorous assessesments, this study finds that the virulent HSV-1 strain McKrae resulted in a low level HSV-1 infection that elicited modest immune responses and transiently modulated SIV infection.